Green initiatives in the maritime industry : environmental perspective - Yap, Liu Chin (2014)
With an increasing awareness towards environmental protection, different maritime stakeholders have expressed concerns about the adverse environmental impacts brought by shipping activities. The pollution and waste created in the process of shipping have imposed environmental burdens and accelerated resource depletion. This situation is set to worsen in the face of intensifying trade globalization. In the effort to combat climate change, shipping firms have taken the initiatives to lessen the environmental damage of their operations while enhancing their performance.